INFLUENCE OF GLYCININ AND Β-CONGLYCININ OF SOYBEAN ON THE PROLIFERATION AND IMMUNE FUNCTION OF SUCKLING PIGLETS PERIPHERAL BLOOD MONONUCLEAR CELLS IN IN VITRO CULTURE - Xu Jun; Z. Anguo; W. Zhisheng; A. Dawei (Journal of Animal and Plant Sciences, 2009)
This experiment studied the effect of different level of purified glycinin and β-conglycinin on proliferation and immune function of peripheral blood monomuclear cells (PBMC) of suckling pigs in vitro. The results indicated that the amount of cells in the group of glycinin and β-conglycinin increased gradually. The cell 3-(4,5)-dimethylthiahiazo (-z-yl)-3,5-di-phenytetrazolumromide (MTT) absorption at 570 nm wavelength was significantly affected by glycinin and β-conglycinin concentration (P<0..01). β-conglycinin had a significant positive correlation with interleukin -2, interleukin-6, interferon-γ and immune globulin A. In summary, glycinin and β-conglycinin could promote PBMC of suckling pigs to transform and proliferate in vitro culture, β-conglycinin could promote PBMC of suclking pigs to produce cytokine with IL-2, INF-γ, IL-6 and raise the level of immunoglobulin. The results showed that the antigen of β-conglycinin was stronger than that of glycinin.
Keywords: immune function; peripheral blood mononuclear cells; piglet; proliferation; soybean.